2019
DOI: 10.1002/qute.201970031
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Quantum Algorithms for GHZ and W States, and Implementation on the IBM Quantum Computer (Adv. Quantum Technol. 5‐6/2019)

Abstract: Entanglement is a fundamental resource in quantum information and technology. In article number 1900015, Clément Javerzac‐Galy and co‐workers investigate efficient new algorithms to create N‐qubit Greenberger–Horne–Zeilinger (GHZ) and W states with time‐complexity scaling linearly and logarithmically in N. Quantum circuits are implemented on the IBM quantum computer up to N = 16, and entanglement is investigated through tomography (and other methods) as shown in the cover picture. While the fidelity decreases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…We finally showed that in the extreme situation of the inner radius coalescing with the outer radius, the electron becomes a classical particle. With the increasing interest in spherically confined multi‐electron atoms in recent years, it is worth mentioning that the GPS method developed here could potentially serve as a powerful numerical tool for solving the one‐electron equation in other sophisticated approximations for confined multi‐electron systems, for example, the self‐consistent Hartree–Fock method [49–51] and the density‐functional theory [52–55].…”
Section: Discussionmentioning
confidence: 99%
“…We finally showed that in the extreme situation of the inner radius coalescing with the outer radius, the electron becomes a classical particle. With the increasing interest in spherically confined multi‐electron atoms in recent years, it is worth mentioning that the GPS method developed here could potentially serve as a powerful numerical tool for solving the one‐electron equation in other sophisticated approximations for confined multi‐electron systems, for example, the self‐consistent Hartree–Fock method [49–51] and the density‐functional theory [52–55].…”
Section: Discussionmentioning
confidence: 99%
“…It guarantees that ( = , ) = 0 at the boundary. This factor has been successfully used in previous variational studies of atoms confined by padded spherical walls [28] and becomes the usual cut-off term for an infinitely hard wall when = 1, as discussed in [12]. This type of cut-off function was found to provide accurate results.…”
Section: The Trial Wave Functionmentioning
confidence: 99%